Gemin5 delivers snRNA precursors to the SMN complex for snRNP biogenesis - Yong, Jeongsik (2010)
The SMN complex assembles Sm cores on snRNAs, a key step in the biogenesis of snRNPs, the spliceosome's major components. Here, using SMN complex inhibitors identified by high throughput screening and a ribo-proteomic strategy on formaldehyde crosslinked RNPs, we dissected this pathway in cells. We show that protein synthesis inhibition impairs the SMN complex, revealing discrete SMN and Gemin subunits and accumulating an snRNA precursor (pre-snRNA)-Gemin5 intermediate. By high throughput sequencing of this transient intermediate's RNAs, we discovered the previously undetectable precursors of all the snRNAs and identified their Gemin5 binding sites. We demonstrate that pre-snRNA 3′-sequences function to enhance snRNP biogenesis. The SMN complex is also inhibited by oxidation and we show that it stalls an inventory-complete SMN complex containing pre-snRNAs. We propose a stepwise pathway of SMN complex formation and snRNP biogenesis, highlighting Gemin5's function in delivering pre-snRNAs as substrates for Sm core assembly and processing.